2022
DOI: 10.3389/fmars.2021.789572
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Health Risk of Trace Metals in Fishes in Liaodong Bay, China, From 2015 to 2020

Abstract: Due to their toxicity, non-biodegradability, and biological amplification in the food chain, heavy metal accumulation in humans via the consumption of fishes has become a problem. In this study, we analyzed the concentrations of six trace metals (Cd, Cr, Cu, Ni, Pb, Zn) in 12 marine fish species collected from Liaodong Bay, China, from 2015 to 2020, to understand the pollution status of the bay and evaluate the impact of fish consumption on human health. In addition, 5 fish species with the potential to serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Hence, it is suggested that these three fish species show no adverse human health effects upon consumption. Wang et al 49 observed health risk issues associated with trace metals, i.e., Cd, Cr, Cu, Ni, Pb, and Zn in twelve marine fish occurring at Liaodong Bay on the China coast. They found that the total target hazard quotient (TTHQ) values were greater than one (TTHQ > 1) in these fishes and concluded that Chinese people were susceptible to high health risks by their consumption, which is consistent with our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is suggested that these three fish species show no adverse human health effects upon consumption. Wang et al 49 observed health risk issues associated with trace metals, i.e., Cd, Cr, Cu, Ni, Pb, and Zn in twelve marine fish occurring at Liaodong Bay on the China coast. They found that the total target hazard quotient (TTHQ) values were greater than one (TTHQ > 1) in these fishes and concluded that Chinese people were susceptible to high health risks by their consumption, which is consistent with our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight known breeding grounds of spotted seals worldwide, Liaodong Bay, in northern parts of Bohai Sea, is the southmost and has hundreds of adults raising their cubs there during winter seasons (Hu et al, 2013;Wu et al, 2022). However, the Bohai Sea has several offshore oil platforms that often contribute to the discharge of anthropogenic pollutants in the ocean (Wang et al, 2022). High median concentrations of trace elements such as Cr (27.07 mg kg -1 ), Cu (10.35 mg kg -1 ), Zn (38.90 mg kg -1 ), Pb (21.16 mg kg -1 ), and As (9.78 mg kg -1 ) were found in sediments from Liaodong Bay .…”
Section: Introductionmentioning
confidence: 99%